Improving new product development (NPD) process by analyzing failure cases - Yeon-Hak Kim (Asia Pacific Journal of Innovation and Entrepreneurship, 2017)
Purpose - The purpose of this study is to develop an appropriate new product development (NPD) process of Company “T”, a medium-sized firm, by analyzing the existing NPD process and failure cases of the Company. Design/methodology/approach - The proposed research framework is as follows: first, prospective studies of the NPD process are performed using the existing literature and preliminary references; second, comparative analysis between the current processes and a NPD process is performed; third, phase-based evaluations upon failed product cases are conducted with a NPD process so as to identify the abridged steps and root-causes of failures; finally, renewed priorities are set forth by utilizing the analytic hierarchy process analysis and questionnaire analysis upon the above identified causes of failures. Findings - The resulting accomplishments include the establishment of NPD processes that resonates with the current states of Company “T”, which, in turn, ensures the increase of efficiency, the decrease in development duration and the strategy of capacity-concentration and priority-selection. Originality/value - As Company “T”’s development process is outdated and products are developed without adequate market information research and feasibility analysis, the percentage of failed development project is as high as 87 per cent. Thus, this study aims to develop an appropriate NPD process of Company “T” by analyzing the existing NPD process and failure cases of the Company.